A modular petri net based architecture to model manufacturing systems exhibiting resource and timing uncertainties - Hyunsoo Lee; Banerjee, A. (2009 IEEE International Conference on Automation Science and Engineering, 2009)
Modeling of a manufacturing system consisting of many processes typically requires extensive assumptions and approximations during design stage. A modeling methodology that can capture the complexities of a process and existing uncertainties in a reconfigurable manner is needed to reduce the extent of the assumptions and approximations. A Petri net approach is one of the effective methodologies for modeling reconfigurable manufacturing system (RMS). A fuzzy colored Petri net with stochastic time delay (FCPN-std) concept is proposed here, which is shown as an effective modeling methodology to incorporate different types of uncertainties using fuzzy logic and stochastic time delay. A 5-stage modeling method is proposed to capture complexities in manufacturing processes with the help of FCPN-std and parametric Petri net modules.